ACADEMICIAN NIKOLAY VASILIEV: LIFE IN SCIENCE - Е. L. Choinzonov; N. V. Cherdyntseva; S. A. Nekrylov (Сибирский онкологический журнал, 2016)
The article presents a biographical sketch of the outstanding Russian scientist, academician of RAMS, Professor N.V. Vasiliev.